Effect of trypanosome infection on livestock health and production traits in northern Ivory Coast - Schuetterle, A.; Coulibaly, L.; Diarrassouba, I.; D'Ieteren, G.D.M.; Itty, P.; Konin, N.; Maehl, H.M.; Mahamat, B.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Thorpe, W.R.; et al. (OAU/STRC, 1988)
Estimates the prevalence, species and intensity of trypanosome infection found in cattle and sheep breeds and age groups, and the effect of these infections on health and production traits in northern Ivory Coast